Perancangan Media Pembelajaran Bercocok Tanam Hidroponik Berbasis Interaktif 2D - Citra Ratih Prameswari; Imsakul Rahma Fitri (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The rapid advancement of technology is evidenced by numerous innovations that simplify human tasks, particularly in the agricultural sector. Various farming methods are offered to produce fruits and vegetables without using chemical pesticides. Hydroponic techniques have been implemented to maximize crop yields without the use of chemicals in the plant care process. The community in Barean Village, Ploso, Pacitan Regency still relies on conventional farming methods. Conventional farming methods, apart from requiring large areas, also have adverse environmental and health impacts due to the use of chemical pesticides. Farmer have to spend quite a lot of capital to provide large amounts of fertiliser to treat the plants in their fields. The results obtained from conventional farming methods are not worth the capital spent. Hydroponic farming metode is an agricultural method that uses water as a growing medium. This method is recognised as an environmentally friendly method, as it uses water and nutrient solutions as a substitute for nutrients found in soil. Autor introduces hydroponic cultivation methods to the public through a digital platform. People from all walks of life can learn farming techniques using the hydroponic method, as it is more visually appealing, and can be operated interactively. Hydroponic techniques can be effectively learned through this 2D interactive media, which provides comprehensive knowledge about the hydroponic method, equipment, materials, and proper cultivation methods. The final section of this interactive media features a simple quiz to assess knowledge for novice farmers. The design of 2D Interactive Based Hydroponic Farming Learning Media is expected to be an attraction for the community in the field of agriculture. The development of this 2D Interactive Hydroponic Farming Educational Media is intended to serve as a solution for hydroponic cultivation education, thereby maximizing agricultural productivity.